Strengthening Sharia Accountability and Transparancy for the Optimization of Cash Waqf Linked Sukuk - Erny Arianty; M. Luthfi Mahrus; Miftahul Hadi; Iin Indrawati (Riset Akuntansi dan Keuangan Indonesia, 2023)
This research is motivated by the fact that the cash waqf linked Sukuk fund collection has not met expectations, where one of the causes is the low implementation of accountability and transparency. This study aims to analyze strategies to overcome problems and strengthen the implementation of sharia perspective accountability and transparency as an effort to optimize CWLS fundraising. The method used is the theme approach and Analytical Network Process (ANP). Data was collected through the FGD method and distributing questionnaires to several informants from BWI, nazir (waqf fund managers), Islamic Banks as LKS Collecting Cash Waqf Funds (LKSPWU), the government, and KNEKS. The results show that the main strategy in overcoming the problem is to increase the monitoring and supervision function of regulators and the government. The main strategy for strengthening accountability and transparency is competency development in related fields and setting rules for the types of information that must be conveyed to the public.